PREJUDICE AND HOSTILITY: SOME PERSPECTIVE - - Faturochman (Buletin Psikologi, 1993)
In the United the States the largest segment of studies has predictively been the descriptive or documenttaion of racial prejudice for over four decades (Crosby, Bromley and Saxe, 1984). The differential treatment of individuals based on their gorup membership, especially race, can be measured by discrriminatory behaviour and prejudiced attitudes. The pre-sumption of certain sttributes in individuals solely on the basis of a particular group, called stereotyping, is another form of prejudice that is a useful measure for racism.